Palm Kernel Cake Extracts Obtained from the Combination of Bacterial Fermentation and Enzymic Hydrolysis Promote Swine Small Intestine IPEC-J2 Cell Proliferation and Alleviate LPS-Induced Inflammation In Vitro - Hui Zeng; Jingna Miao; Jinghong Liao; Zhiyuan Sui; Meixin Hou; Suqin Hang (MDPI AG, 2024)
Co-fermentation with bacteria and enzymes can reduce sugar content in palm kernel cake (PKC); however, the chemical changes and their effects on cell functionality are unclear. This study investigated the active components in pre-treated PKC extracts and their effects on pig small intestine IPEC-J2 cell proliferation and LPS-induced inflammation. The extracts contained 60.75% sugar, 36.80% mannose, 1.75% polyphenols and 0.59% flavone, as determined by chemical analyses, suggesting that the extracts were palm kernel cake oligosaccharides (PKCOS). Then, we found that 1000 µg/mL PKCOS counteracted the decrease in cell viability (CCK8 kit) caused by LPS induction by 5 µg/mL LPS (p < 0.05). Mechanistic studies conducted by RNA-seq and qPCR analyses suggested PKCOS promoted cell proliferation through the upregulation of TNF-α, PI3KAP1, MAP3K5 and Fos in the PI3K/MAPK signalling pathway; alleviated inflammation caused by LPS via the downregulation of the target genes Casp3 and TNF-α in association with apoptosis; and regulated the expression of the antioxidant genes SOD1, SOD2 and GPX4 to exert positive antioxidant effects (p < 0.05). Furthermore, PKCOS upregulated SLC5A1 (encoding SLGT1), HK and MPI in the glycolytic pathway (p < 0.05), suggesting cell survival. In summary, PKCOS has positive effects on promoting swine intestine cell proliferation against inflammation.